Identifying behavioural changes in ALS: Validation of the Beaumont Behavioural Inventory (BBI). Issue 1 (2nd January 2017) - Elamin, Marwa; Pinto-Grau, Marta; Burke, Tom; Bede, Peter; Rooney, James; O'Sullivan, Meabhdh; Lonergan, Katie; Kirby, Emma; Quinlan, Emma; Breen, Nadia; Vajda, Alice; Heverin, Mark; et al.
Abstract: Objective : Behavioural changes are an important part of amyotrophic lateral sclerosis (ALS). However, most tools do not account for the influence of motor impairment. Furthermore, they do not fully measure the broad range of behavioural changes specific to ALS. This study aimed to develop and validate an ALS specific behavioural inventory, the Beaumont Behavioural Inventory (BBI). Methods : The BBI was validated in a cohort of ALS patients ( n = 85) and 78 age-, gender-, and education-matched controls. The scale was validated against the Frontal Systems Behaviour Scale (FrSBe) and The Frontal Assessment Battery (FAB) for convergent validity, and against other non-behavioural measures to assess discriminant validity. Reliability was assessed with Cronbach's alpha. Results : The instrument showed high internal consistency (Cronbach's alpha value =0.891). BBI scores highly correlated with the FrSBe and moderately with the FAB. However, the measure was independent from non-behavioural measures. Using a cut-off score of 7 for mild behavioural changes, the BBI displayed high sensitivity and specificity (87.9% and 78.85%, respectively). The cut-off score for moderate changes, consistent with a diagnosis of ALS-FTD, is set at 22.5, showing 90% sensitivity and 96% specificity. Discussion : The BBI is a sensitive and specific tool to assess the entire behavioural spectrum of ALS.